Adjuvant chemotherapy with fluorouracil plus folinic acid vs gemcitabine following pancreatic cancer resection: a randomized controlled trial - Neoptolemos, John P.; Stocken, Deborah D.; Bassi, Claudio; Ghaneh, Paula; Cunningham, David; Goldstein, David; Padbury, Robert; Moore, Malcolm J.; Gallinger, Steven; Mariette, Christophe; Wente, Moritz N.; Izbicki, Jakob R.; et al. (The journal of the American Medical Association, 2010)
Adjuvant fluorouracil has been shown to be of benefit for patients with resected pancreatic cancer. Gemcitabine is known to be the most effective agent in advanced disease as well as an effective agent in patients with resected pancreatic cancer.To determine whether fluorouracil or gemcitabine is superior in terms of overall survival as adjuvant treatment following resection of pancreatic cancer.The European Study Group for Pancreatic Cancer (ESPAC)-3 trial, an open-label, phase 3, randomized controlled trial conducted in 159 pancreatic cancer centers in Europe, Australasia, Japan, and Canada. Included in ESPAC-3 version 2 were 1088 patients with pancreatic ductal adenocarcinoma who had undergone cancer resection; patients were randomized between July 2000 and January 2007 and underwent at least 2 years of follow-up.Patients received either fluorouracil plus folinic acid (folinic acid, 20 mg/m2, intravenous bolus injection, followed by fluorouracil, 425 mg/m2 intravenous bolus injection given 1-5 days every 28 days) (n = 551) or gemcitabine (1000 mg/m2 intravenous infusion once a week for 3 of every 4 weeks) (n = 537) for 6 months.Primary outcome measure was overall survival; secondary measures were toxicity, progression-free survival, and quality of life.Final analysis was carried out on an intention-to-treat basis after a median of 34.2 (interquartile range, 27.1-43.4) months' follow-up after 753 deaths (69%). Median survival was 23.0 (95% confidence interval [CI], 21.1-25.0) months for patients treated with fluorouracil plus folinic acid and 23.6 (95% CI, 21.4-26.4) months for those treated with gemcitabine (χ21 = 0.7; P = .39; hazard ratio, 0.94 [95% CI, 0.81-1.08]). Seventy-seven patients (14%) receiving fluorouracil plus folinic acid had 97 treatment-related serious adverse events, compared with 40 patients (7.5%) receiving gemcitabine, who had 52 events (P < .001). There were no significant differences in either progression-free survival or global quality-of-life scores between the treatment groups.Compared with the use of fluorouracil plus folinic acid, gemcitabine did not result in improved overall survival in patients with completely resected pancreatic cancer.clinicaltrials.gov Identifier: NCT00058201